2008
DOI: 10.1002/maco.200804143
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Cr–C electroplating between 400 and 900 °C in air

Abstract: The high temperature oxidation of Cr-C electroplated on a steel substrate was studied at 400-900 8C in air. Before oxidation, the deposit consisted primarily of C-supersaturated, amorphous Cr grains. During oxidation, oxygen diffused inward, while Cr and the substrate elements such as Fe diffused outward. Carbon tended to escape, but some of it remained and existed mainly as graphite throughout the oxide layer and the Cr-C electrodeposit. A Cr 2 O 3 oxide layer having dissolved Fe ions formed on the unoxidized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Subramanian et al [22] reported that brush-plated Ni coatings have better corrosion resistance than direct current magnetron sputtering deposited Ni. It has been pointed out that the formation of internal micro-cracks, the unstable bath composition, and the low current efficiency are the major drawbacks for the commercialization of trivalent hard chromium plating [23]. In a study of the influence of rare earth element addition on residual stress of the Fe-based coating, Guo et al [24] demonstrated that the addition of rare earth elements transforms the residual stress from tensile to compressive, leading to a reduced number of cracks in the coatings.…”
Section: Of 10mentioning
confidence: 99%
See 2 more Smart Citations
“…Subramanian et al [22] reported that brush-plated Ni coatings have better corrosion resistance than direct current magnetron sputtering deposited Ni. It has been pointed out that the formation of internal micro-cracks, the unstable bath composition, and the low current efficiency are the major drawbacks for the commercialization of trivalent hard chromium plating [23]. In a study of the influence of rare earth element addition on residual stress of the Fe-based coating, Guo et al [24] demonstrated that the addition of rare earth elements transforms the residual stress from tensile to compressive, leading to a reduced number of cracks in the coatings.…”
Section: Of 10mentioning
confidence: 99%
“…In a study of the influence of rare earth element addition on residual stress of the Fe-based coating, Guo et al [24] demonstrated that the addition of rare earth elements transforms the residual stress from tensile to compressive, leading to a reduced number of cracks in the coatings. The prevention of the internal micro-cracks could significantly assist the commercialization of trivalent hard chromium plating due to better current efficiency from lower amounts of micro-cracks [23]. Ghaziof et al [25] claimed that thermal treatments could promote the precipitation of Cr 23 C 6 , and thereby enhance the hardness of the amorphous Cr-C alloy coatings electrodeposited using direct current magnetron sputtering on a copper substrate.…”
Section: Of 10mentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, the electrodeposition technique excels for its simplicity, low cost and possibility of large-scale production 3 , apart from making films with great hardness and mechanical resistance in addition to excellent optical and thermal proprieties 6 . Regarding the type of material, black chromium is one of the most used coatings for the efficient conversion of solar energy into thermal energy, that along with the electrodeposition technique compose the set of fundamental characteristics for high performance 7 .…”
Section: Introductionmentioning
confidence: 99%
“…During the chromium plating process, hydrogen evolution from the reduction of protons promotes the formation of microcracks in the chromium layer. 21 Samples were also analysed by FE-SEM after exposure to Cu+Cl electrolyte. Layers are galvanically coupled in order to improve the corrosion resistance of the overall multilayer system.…”
Section: Resultsmentioning
confidence: 99%